2016
DOI: 10.4158/ep161332.or
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Primary Aldosteronism in an Urban Hypertensive Population

Abstract: Abstract:Objective: To determine the prevalence of Primary Aldosteronism (PA) in hypertensive patients presenting to the primary care clinic at The Mount Sinai Hospital, regardless of the degree of hypertension and to identify clinical criteria that should prompt screening for PA.Methods: An ARR (cutoff ≥20, with PAC ≥ 10 and suppressed renin) was used to prospectively screen 296 hypertensive patients (BP ≥ 140/90) over the age of 18 from August 2012 through May 2013.Subjects who screened positive then underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Käyser et al [33] systematically reviewed 39 studies comprising 42510 patients with 36614 patients from hypertension units (26 studies) and 5896 patients from primary care 13 studies) and reported a prevalence of PA in hypertension referral centres ranging from 0.7% to 29.8% and from 3.2% to 12.7% in primary care. An additional 9 studies on the prevalence of PA in referred patients have since been published [33,[46][47][48][49][50][51][52][53][54], bringing the median prevalence of PA in 55045 referred patients with hypertension in all 36 studies to date to 7.0%.…”
Section: Prevalence Of Pa In Populations With Hypertensionmentioning
confidence: 99%
“…Käyser et al [33] systematically reviewed 39 studies comprising 42510 patients with 36614 patients from hypertension units (26 studies) and 5896 patients from primary care 13 studies) and reported a prevalence of PA in hypertension referral centres ranging from 0.7% to 29.8% and from 3.2% to 12.7% in primary care. An additional 9 studies on the prevalence of PA in referred patients have since been published [33,[46][47][48][49][50][51][52][53][54], bringing the median prevalence of PA in 55045 referred patients with hypertension in all 36 studies to date to 7.0%.…”
Section: Prevalence Of Pa In Populations With Hypertensionmentioning
confidence: 99%
“…Although reports of PA prevalence among patients with hypertension have been heterogeneous due to the vast differences in PA definition between studies, findings consistently suggest that PA prevalence increases in parallel with hypertension severity, ranging from 11–22% in the individual with treatment-resistant hypertension ( Table 1 ) 14 27 36 41 42 43 44 45 46 . On average, only under 3–4% of individuals with treatment-resistant hypertension are screened for PA 14 16 47 48 .…”
Section: Introductionmentioning
confidence: 99%
“…However, over the past three decades, substantial evidence has emerged showing that PA is more common than initially thought. Studies conducted in the primary care setting with the aim of actively looking for PA have reported a prevalence of 3 to 14% ( Table 1 ) 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 . The prevalence estimates vary depending on the diagnostic threshold used to define PA, with more stringent thresholds unsurprisingly associated with a lower prevalence 27 .…”
Section: Introductionmentioning
confidence: 99%